Sexual Dimorphism of Dexamethasone as a Prophylactic Treatment in Pathologies Associated With Acute Hypobaric Hypoxia Exposure - Chanana, Neha; Palmo, Tsering; Sharma, Kavita; Kumar, Rahul; Shah, Bhushan; Mahajan, Sudhanshu; Palleda, Girish M.; Gupta, Mohit D.; Kukreti, Ritushree; Faruq, Mohammad; Thinlas, Tashi; Graham, Brian B.; et al. (Frontiers in Pharmacology, 2022)
Dexamethasone can be taken prophylactically to prevent hypobaric hypoxia-associated disorders of high-altitude. While dexamethasone-mediated protection against high-altitude disorders has been clinically evaluated, detailed sex-based mechanistic insights have not been explored. As part of our India-Leh-Dexamethasone-expedition-2020 (INDEX2020) programme, we examined the phenotype of control (n=14) and dexamethasone (n=13) groups, who were airlifted from Delhi ( 225 m elevation) to Leh, Ladakh ( 3500 m), India, for three days. Dexamethasone 4 mg twice daily significantly attenuated the rise in blood pressure, heart rate, pulmonary pressure, and drop in SaO2 resulting from high-altitude exposure compared to control-treated subjects. Of note, the effect of dexamethasone was substantially greater in females than males, in whom the drug had relatively little effect. Thus, for the first time, this study shows a sex-biased regulation by dexamethasone of physiologic parameters resulting from the hypoxic environment of high-altitude, which impacts the development of high-altitude pulmonary hypertension and acute mountain sickness. Future studies of cellular contributions towards sex-specific regulation may provide further insights and preventive measures in managing sex-specific, high-altitude-related disorders.